Perancangan Sistem Pemantauan Kelembaban Tanah, Kelembaban Udara, dan Suhu Udara pada Lahan Pembibitan Kakao Menggunakan Mikrokontroller Berbasis Internet of Things (Strudi Kasus: Pembibitan Efendi Farm) - Haq, Fariz Abdillah; Pramuntadi, Andri; Wijaya, Dhina Puspasari; Danianti, Dita (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to design a monitoring system for soil moisture, air humidity, and air temperature in a cocoa seedling farm using a microcontroller-based Internet of Things (IoT). The system was implemented at Efendi Farm, which houses 20,000 cocoa seedlings. Monitoring is conducted using soil moisture sensors and DHT22 sensors for temperature and humidity, with data displayed on an LCD and sent to an Android application via Firebase. The system also includes notifications via buzzer and Telegram, as well as data logging using Google Spreadsheet. The results indicate that the system effectively monitors environmental conditions in real-time and efficiently.